Pengaruh Capital Adequacy Ratio (CAR), Biaya Operasional terhadap Pendapatan Operasional (BOPO), dan Non-Performing Loan (NPL) terhadap Kinerja Keuangan pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2019–2022 - Agitha, Tilana Oktavia (Jurnal KIAFE, 2024)
This study examines the effects of profitability, audit opinion, and firm size on audit delay in energy-sector companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The study employs a quantitative approach using secondary data obtained from audited financial statements and annual reports. The sample was selected through purposive sampling and initially consisted of 17 companies with 85 firm-year observations. After eliminating 28 outlier observations, 57 observations were included in the final analysis. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 29. The results show that profitability and audit opinion have no significant effects on audit delay, while firm size has a negative and significant effect. Simultaneously, profitability, audit opinion, and firm size significantly affect audit delay. The coefficient of determination is 25.8%, indicating that the research model explains 25.8% of the variation in audit delay.